Pengaruh Keharmonisan Dan Tingkat Sosial Ekonomi Keluarga Terhadap Perilaku Keagamaan Anak - Irwan Ruswandi (Rayah Al-Islam, 2020)
This study aims to explain: family harmony, family socioeconomic level, religious behavior of children in Cikaret Village, Kebonpedes District, Sukabumi. The influence of family harmony on children's religious behavior. The influence of the socioeconomic level of the family on the religious behavior of children and the effect of harmony and the socioeconomic level of the family together on the religious behavior of children in Cikaret Village, Kebonpedes District, Sukabumi. The research approach used in this research is quantitative. The method used in this research is a survey method. This research includes a quantitative approach using a correlation design. The population of this research is the Cikaret village community with a sample of 62 respondents. The main data collection technique used is through a questionnaire, then supported by interviews, observation and documentation study. The prerequisite analysis test used the normality test and linearity test, the hypothesis test used the Product moment correlation test. The results showed that family harmony in Cikaret Village, Kebonpedes District, Sukabumi was in the high or good category. The socioeconomic level of the family is in the low category. The overall religious behavior of children is in the good category. There is a positive influence on family harmony on children's religious behavior. There is a positive influence on the socio-economic level of the family on the religious behavior of children in Cikaret Village, Kebonpedes District, Sukabumi. There is a positive and significant influence between family harmony and the socioeconomic level of the family on the religious behavior of children in Cikaret Village, Kebonpedes District, Sukabumi which is indicated by Fcount (17.006)> Ftable (3.15). The significance value of F for the variable family harmony (X1) and the socioeconomic level of the family (X2) is 0.000 and this value is smaller than. probability 0.05 (0.000 <0.05). So that in this test it shows that Ha is accepted and Ho is rejected. This means that there is a positive and significant influence between family harmony (X1) and family socioeconomic level (X2) on children's religious behavior (Y) in Cikaret Village, Kebonpedes District, Sukabumi.